2014
DOI: 10.1371/journal.pone.0111798
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Haplotypes of the Dopamine Receptor Gene (DRD2) and ANKK1 Gene Polymorphisms in Patients with Alcohol Dependence – Preliminary Report

Abstract: Suicide is a significant public health issue and a major cause of death throughout the world. According to WHO it accounts for almost 2% of deaths worldwide. The etiology of suicidal behavior is complex but the results of many studies suggest that genetic determinants are of significant importance. In our study,- we have analyzed selected SNPs polymorphisms in the DRD2 and ANKK1 genes in patients with alcohol dependence syndrome (169 Caucasian subjects) including a subgroup of individuals (n = 61) who have exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
17
3
3
Order By: Relevance
“…We found that our results are agreement with those of previous studies that indicate an association between Taq1A and suicidal behavior [12, 22]. In 2009, Suda et al [12], in a case-control study (120 suicide attempters and 123 controls), reported an association of the A2 allele of Taq1A (rs1800497T) in suicide attempters in Japan.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that our results are agreement with those of previous studies that indicate an association between Taq1A and suicidal behavior [12, 22]. In 2009, Suda et al [12], in a case-control study (120 suicide attempters and 123 controls), reported an association of the A2 allele of Taq1A (rs1800497T) in suicide attempters in Japan.…”
Section: Discussionsupporting
confidence: 92%
“…In 2009, Suda et al [12], in a case-control study (120 suicide attempters and 123 controls), reported an association of the A2 allele of Taq1A (rs1800497T) in suicide attempters in Japan. Recently, Jasiewicz et al [22] in Poland evaluated people with alcohol dependence and suicide attempt ( n = 61) and reported a haplotype that includes Taq1A (rs1800497T) associated with suicidal behavior. These positive associations and the results of the present study suggest a possible role of ANKK1 in suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Biochemical and genetic changes may favor the development of suicidal behavior, specifically in people with alcohol-related disorders. 32,36,59 A study that investigated the presence of abnormalities in the endocannabinoid system of suicidal people with alcohol-related disorders showed that there is higher levels of CB1 receptors in the ventral striatum and G protein signaling mediated by the CB1 receptor between alcoholics who committed suicide. 32 Some genetic changes act on the dopaminergic 59 and the serotoninergic 36 system, which may result in a higher probability of developing suicidal behavior in alcoholics.…”
Section: Cross-sectionalmentioning
confidence: 99%
“…It was shown that T-allele carriers have a lower density of DRD2 receptors [32]. The DRD2 rs1800497 polymorphism is associated with impulsivity and suggested to be related to suicidal attempts [33,34]. The enzyme catechol-O-methyltransferase (COMT) plays an important role in dopamine metabolism.…”
Section: Introductionmentioning
confidence: 99%